Emergent Life Cycle: The Tension Between Knowledge Change and Knowledge Retention in Open Online Coproduction Communities - Kane, Gerald C.; Johnson, Jeremiah; Majchrzak, Ann (Management Science, 2014)
Online coproduction communities often face a challenge of whether to change or retain the knowledge they have created. Disparate and often conflicting theoretical models have been used to explain how these communities respond to this tension. We conducted a case study of how one online coproduction community—the nine-year history of the Wikipedia article on autism—handles this tension. We find that the nature of the change–retain tension and the community’s response to it fluctuates considerably over the life of the community. These changes bear striking similarities to processes associated with traditional software development life cycles, despite the absence of traditional control mechanisms. What initially appear to be conflicts in the extant literature actually describe different roles and production focus at the different stages of development. Disruptive events signal the need for the community to shift production focus, which often involves members joining and leaving the production process, rather than adopting new roles. This paper was accepted by Sandra Slaughter, information systems.